The Effect of Product Innovation and Market Orientation on Business Performance - Mutianto, Pradwipa; Hidayati, Retno (LifeSciFi, 2024)
This study uses competitive advantage as an intervening variable in the Solo Residency coffee shop industry to examine how product innovation and market orientation affect business performance. The performance of the coffee shop in Solo Residency, which is still below expectations, is the issue brought up in this study.Coffee shop managers or owners who have been in business for at least six months make up the study's population. A non-probability or non-random sampling technique is employed in this investigation. Purposive sampling methods were used for the sampling. A questionnaire was given to the respondents as part of the study's data collection strategy. 170 questionnaire responses were analyzed using the Structural Equation model (SEM) using AMOS 26. According to the study's findings, competitive advantage significantly improves company success. Business performance is significantly improved by product innovation. Competitive advantage is significantly enhanced by product innovation. Market orientation has very little beneficial effect on business success. Coffee shops in Solo Residency can successfully attain their competitive advantage if they implement market orientation, since it has been shown to greatly increase competitive advantage.